2023
DOI: 10.1002/jhm.13074
|View full text |Cite
|
Sign up to set email alerts
|

Building a thriving academic hospitalist workforce: A rapid qualitative analysis identifying key areas of focus in the field

Abstract: Background: The hospitalist workforce has been at the forefront of the pandemic and has been stretched in both clinical and nonclinical domains. We aimed to understand current and future workforce concerns, as well as strategies to cultivate a thriving hospital medicine workforce.Design, Setting, and Participants: We conducted qualitative, semistructured focus groups with practicing hospitalists via video conferencing (Zoom). Utilizing components from the Brainwriting Premortem Approach, attendees were split i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…The data produced during the session is immediately accessible and can be discussed within the group to consolidate ideas, identify the most valuable, and rank order them to support real-time decision making. 11 Two examples of virtual brainwriting sessions pertinent to hospital medicine include a study by Steenbruggen et al 11 that used virtual brainwriting to design a framework to enhance the quality of hospital-based physiotherapy in the Netherlands and a study by Kulkarni et al 5 that gathered insights from hospitalists regarding potential workforce challenges over the next 3 years. These teams adapted the brainwriting method to fit the needs of their projects by using multiple breakout rooms to keep the group size <5 people, recording the sessions, and having moderators collect field notes to support future qualitative analyses.…”
Section: Brainwriting Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data produced during the session is immediately accessible and can be discussed within the group to consolidate ideas, identify the most valuable, and rank order them to support real-time decision making. 11 Two examples of virtual brainwriting sessions pertinent to hospital medicine include a study by Steenbruggen et al 11 that used virtual brainwriting to design a framework to enhance the quality of hospital-based physiotherapy in the Netherlands and a study by Kulkarni et al 5 that gathered insights from hospitalists regarding potential workforce challenges over the next 3 years. These teams adapted the brainwriting method to fit the needs of their projects by using multiple breakout rooms to keep the group size <5 people, recording the sessions, and having moderators collect field notes to support future qualitative analyses.…”
Section: Brainwriting Methodsmentioning
confidence: 99%
“…The authors reported that the brainwriting method effectively elicited novel insights 11 and facilitated input from all participants. 5 An advantage of the brainwriting method, compared to verbal brainstorming, is the rapid collection of written data and the creation of an environment where everyone feels safe to share, making brainwriting the ideal method for a project premortem.…”
Section: Brainwriting Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitalist groups report burnout, excessive cognitive load, escalating social and clinical complexity of patients, and a perceived lack of respect for their contributions. 1 Meanwhile, hospitalist leaders face intense pressure from health systems to increase productivity, reduce costs, and justify their expenses, especially for nonclinical effort. Navigating these competing agendas can feel daunting, as it may seem that shared values and interests supporting past collaboration have disappeared.…”
Section: Background: An Evolving Landscapementioning
confidence: 99%
“…However, a growing sense of misalignment exists between hospitalists and the institutions funding them. Hospitalist groups report burnout, excessive cognitive load, escalating social and clinical complexity of patients, and a perceived lack of respect for their contributions 1 . Meanwhile, hospitalist leaders face intense pressure from health systems to increase productivity, reduce costs, and justify their expenses, especially for nonclinical effort.…”
Section: Background: An Evolving Landscapementioning
confidence: 99%